2021
DOI: 10.3390/ani11071911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nano Emulsified Vegetable Oil and Betaine on Growth Traits and Meat Characteristics of Broiler Chickens Reared under Cyclic Heat Stress

Abstract: The effects of nano-emulsified vegetable oil (NEVO) and betaine (BET) supplements on growth performance and meat qualities of broilers reared under cyclic heat stress (HS) were investigated. Two hundred and eighty-eight mixed-sex broilers at 21 d were randomly distributed to a 2 × 3 factorial arrangement of treatments formed by two environmental temperatures (thermoneutral (TN; 24 ± 1 °C) and cyclic high-temperature (HT; 35 ± 1 °C)) and three dietary treatments (control (CON), NEVO, and BET). The cumulative pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
2
13
2
Order By: Relevance
“…Protein denaturation, a protein's ability to bind water, tenderness, and springiness were not impacted by treatment because the concentration of hydrogen ions in the muscle of broiler breasts was unaffected by treatment. This contradicts Abudabos et al ( 49 ), who stated that diet only affected breast filets pH at 24 h post-mortem; the control had lower breast pH than betaine, while nano-emulsified plant oil had an intermediate temperature.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Protein denaturation, a protein's ability to bind water, tenderness, and springiness were not impacted by treatment because the concentration of hydrogen ions in the muscle of broiler breasts was unaffected by treatment. This contradicts Abudabos et al ( 49 ), who stated that diet only affected breast filets pH at 24 h post-mortem; the control had lower breast pH than betaine, while nano-emulsified plant oil had an intermediate temperature.…”
Section: Discussionmentioning
confidence: 71%
“…Treatments, sex, or their interactions had no effect on the other color components and derivatives in breast meat. According to Abudabos et al ( 49 ), no treatment effect of nano-emulsified plant oil or betaine was observed in L * , a * , b * , color saturation, hue angle (H°), and a * to b * ratio.…”
Section: Discussionmentioning
confidence: 94%
“…We also determined the texture characteristics of the PM muscle and the results showed that chronic heat stress lead an improvement of hardness but the springiness was decreased. It has been reported that texture properties (hardness, elasticity, cohesion and chewiness) all increased in a cyclic high-temperature treatment [21]. All those results indicate that chronic heat stress reduces the meat quality of PM muscle in broiler.…”
Section: Discussionmentioning
confidence: 74%
“…It value of the PM muscle. It has been reported that all texture properties (hardness, elasticity, cohesion, and chewiness) increased after a cyclic high-temperature treatment [ 22 ]. Similarly, we found that chronic heat stress resulted in an increase in hardness, but the springiness of the PM muscle was decreased.…”
Section: Discussionmentioning
confidence: 99%